Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Keputusan Pembelian: Literature Review Manajemen Pemasaran - Herdiyanti Herdiyanti; Muh. Abduh. Anwar; Klemens Mere; Tri Apriyono; Agus Suyatno (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Quality products are the main key in winning market competition, which in turn will be able to provide higher satisfaction value to consumers. The purpose of this study was to see the effect of product quality and price perceptions on purchasing decisions. The method in this article is a qualitative method with literature study or Library Research. The purpose of this article is to analyze existing theories by looking at their comparison with previous theories in the research literature. The literature used is literature from research results or reviews that are emphasized in national and international scientific articles related to financial management. All articles used are sourced from the electronic literacy data search engine Mendeley and Google scholar. Based on the theory of several articles on the results and discussion, the conclusions in this article are (1) Product quality has a positive effect on consumer purchasing decisions. (2) Price perception has a positive effect on consumer purchasing decisions. Keywords: product quality, price perception, purchasing decisions